A study of the mathematical misconceptions of college freshmen enrolled in Xavier University algebra course in 1974 - Chai, Luz S. Yap (1975)
The purpose of this study was to determine and analyze the mathematical misconceptions of high school students admitted to the XU collegiate study. To be able to achieve this, a study of the Mathematics Entrance Test and the Mathematics Entrance Test result was conducted.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Keywords: Mathematical ability